ASYMPTOMATIC ADRENAL MYELOLIPOMA: A CASE REPORT - Rana Ata ur Rehman; Fazal ur Rehman Khan; Muhammad Muzammil Tahir (Journal of University Medical & Dental College, 2016)
ABSTRACT: Adrenal myelolipoma is a rare benign tumor of adrenal gland. We report a case of 54 years old female, who presented in the urology department of Sheikh Zayed Hospital Lahore, having incidental finding of right supra renal mass on Ultrasound KUB (Kidney, Ureter and Bladder). The abdominal CT showed a 9.0x6.0cm well marginated right adrenal mass, composed predominately of fat. The mass was removed surgically and the specimen was sent to the Histopathology department. On the basis of morphological features, it was diagnosed as myelolipoma of right adrenal gland.